Anatomical variation of the sacroiliac joint carries an increased risk for erosion and bone marrow oedema in axial spondyloarthritis. (9th May 2022) - Ziegeler, Katharina; Ulas, Sevtap Tugce; Poddubnyy, Denis; Proft, Fabian; Rios Rodriguez, Valeria; Rademacher, Judith; Hermann, Kay Geert A; Diekhoff, Torsten
Abstract: Objectives: To assess the impact of joint shape variations on inflammatory lesions on SI joint MRIs in patients with axial spondyloarthritis (axSpA). Methods: A total of 1194 patients from four different prospective cohorts were evaluated, with 684 (57.3%) having sufficient imaging data for inclusion (379 axSpA, 305 controls). All images were evaluated for joint form, erosion, sclerosis, fat metaplasia and bone marrow oedema (BMO) by two independent readers. Logistic regression analyses were used to assess the association of joint form and lesions on imaging for axSpA patients and controls. Results: Atypical joint forms were common in both axSpA (43.5% [154/354]) and control patients (44.2% [134/303]); both intra-articular variants and a crescent joint shape were significantly more common in axSpA patients (18.4% vs 11.6% and 11.0% vs 5.3.%, respectively; P  < 0.001). The axSpA patients with intra-articular joint form variants had 2-fold higher odds of exhibiting erosions [odds ratio (OR) 2.09 (95% CI 1.18, 3.69)] and BMO [OR 1.79 (95% CI 1.13, 2.82)]; this association was not observed in controls. Accessory joints increased the odds for sclerosis in axSpA patients [OR 2.54 (95% CI 1.10, 5.84)] and for sclerosis [OR 17.91 (95% CI 6.92, 46.37)] and BMO [OR 2.05 (95% CI 1.03, 4.07)] in controls. Conclusions: Joint form variations are associated with the presence of inflammatory lesions on SI joint MRIs of axSpA patients. This should be taken into consideration in future research on the interplay of mechanical strain and inflammation in axSpA.